Pengembangan Buku Panduan Identifikasi Arthropoda di Bendungan Pengga sebagai Bahan Ajar Biologi Kelas X MA Manhalul Ma`Arif Darek Kabupaten Lombok Tengah (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2025)
Arthropods are bilateral animals with small body cavities. Pengga Dam, Central Lombok, can be used as a place to carry out tasks to explore the surrounding nature, especially material on the phylum Arthropoda and support it as teaching material. This is what makes researchers interested in finding out what types of arthropods are found in the Pengga Dam area, Central Lombok. The aims of this research are: (1) to find out what types of arthropods are in the Pengga Dam, Central Lombok, (2) to find out the validity of the arthropod identification guidebook at the Pengga Dam, Central Lombok, (3) to find out the response of teachers and students to Arthropod guidebook at Pengga Dam, Central Lombok. This research method is research and development (Research and Development) with the 4D development model developed by Thiangarajan. There were 20 types of arthropods found at the Pengga Dam in Central Lombok. The results of the validity test of the arthropod identification guidebook carried out by material and media experts obtained an average of 71.76% in the "valid" category so that the arthropod identification guidebook teaching materials were suitable for use. in the learning process.. The results of the teacher's response of 73.33% were declared "agree" and the student response of 84.28% was stated to be "strongly agree" so that the teaching material for the arthropod identification guidebook is suitable for use as additional teaching material in learning.